OPTIMUM ALLOCATION OF FUND ACCORDING TO RISK PROPENSITY OF THE INVESTORS: A STUDY BASED ON NIFTY DATA (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
Risk management plays a vital role in portfolio  analysis. It requires adequate knowledge  in finance and application of sophisticated  techniques. In the allocation of fund analysis,  Markowitz mean-variance model is the most  popular one. Later, Sharpe’s single index  model and arbitrage pricing theory have been  developed. But all these techniques have  not considered the risk perception and risk  propensity of the investors. Risk perception  of the investor depends on so many factors  and it ultimately affect risk propensity of the  investors (value system of the investors). In  this study an attempt has been taken to analyse  the approaches of allocation of fund based on  the risk propensity of the investors. The study  is conducted on taking NIFTY 50 securities.  Finally the results of different approaches are  compared with the results of the Markowitz  mean –variance portfolio optimisation.
Keywords: Portfolio Optimisation; Optimistic; Pessimistic; Mean-Variance; Euclidean distance